Economical Organic Senna Alata Skin Balm Prepared Via Infused Oil Method - Salahuddin, Aisya Sofia; Mohd Yasir, Mohd Afnan; Abdul Rahman, Misbahul Muneer (Multidisciplinary Applied Research and Innovation, 2023)
Senna Alata contains tannins, alkaloids, flavonoids, terpenes, anthraquinone, saponins, and phenolics which is beneficial to reduce inflammation in skin with minimal side effects. Senna Alata has been widely used to treat a lot of skin diseases. Commonly, Senna Alata used traditionally to treat skin diseases like ringworm and eczema, but it also can treat diabetes, asthma and more. In modern skin cream, it contains tropical steroid specially medicated to place it on skin which can give harmful effects on user. The price of skin cream using Senna Alata extract in local market also has been risen unreasonably and cause patients with skin disease hard to find effective remedies with affordable price. Therefore, the objective for this study is to extract Senna Alata leaves using infused oil method and used it as an ingredient to produce a skin balm. This study also target the price of skin balm per container below RM 10. Senna Alata oil extraction is initially carried out using infused oil method prior to produce the balm. Lab test is then carried out to measure the hazardous substance (As, Pb, Cd, Zn). The result indicates no presence of those substances in the skin balm produced. The total cost of skin balm per container is RM6.27.